Influence of Two‐Step Heat Treatments on Microstructure and Mechanical Properties of a β‐Solidifying Titanium Aluminide Alloy Fabricated via Electron Beam Powder Bed Fusion. Issue 2 (21st October 2022) - Moritz, Juliane; Teschke, Mirko; Marquardt, Axel; Heinze, Stefan; Heckert, Mirko; Stepien, Lukas; López, Elena; Brueckner, Frank; Walther, Frank; Leyens, Christoph
Abstract : Additive manufacturing technologies, particularly electron beam powder bed fusion (PBF‐EB/M), are becoming increasingly important for the processing of intermetallic titanium aluminides. This study presents the effects of hot isostatic pressing (HIP) and subsequent two‐step heat treatments on the microstructure and mechanical properties of the TNM‐B1 alloy (Ti–43.5Al–4Nb–1Mo–0.1B) fabricated via PBF‐EB/M. Adequate solution heat treatment temperatures allow the adjustment of fully lamellar (FL) and nearly lamellar (NL‐β) microstructures. The specimens are characterized by optical microscopy and scanning electron microscopy (SEM), X‐ray computed tomography (CT), X‐ray diffraction (XRD), and electron backscatter diffraction (EBSD). The mechanical properties at ambient temperatures are evaluated via tensile testing and subsequent fractography. While lack‐of‐fusion defects are the main causes of failure in the as‐built condition, the mechanical properties in the heat‐treated conditions are predominantly controlled by the microstructure. The highest ultimate tensile strength is achieved after HIP due to the elimination of lack‐of‐fusion defects. The results reveal challenges originating from the PBF‐EB/M process, for example, local variations in chemical composition due to aluminum evaporation, which in turn affect the microstructures after heat treatment. For designing suitable heat treatment strategies, particular attention should therefore be paid to the microstructural characteristics associated with additive manufacturing. Abstract : Herein, the effects of hot isostatic pressing (HIP) and subsequent two‐step heat treatments on the microstructure and mechanical properties of the TNM‐B1 alloy fabricated via electron beam powder bed fusion (PBF‐EB/M) are investigated. While lack‐of‐fusion defects are the main causes of failure in the as‐built condition, the mechanical properties in the heat‐treated conditions are predominantly controlled by the microstructure.